Abortus pada Ibu Hamil yang Terinfeksi COVID-19 dengan Gejala Berat di RSUD Tiom Kabupaten Lanny Jaya Provinsi Papua - Pratiwi, Ervina (Nommensen Journal of Medicine, 2022)
The COVID-19 outbreak is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The disease attacks many groups and pregnant women groups are one of a high risk groups, due to changes in the immune system and cardiorespiratory system in pregnant women. The main symptoms of COVID-19 experienced by pregnant women are same as those experienced by non-pregnant women, like fever, cough and shortness of breath. The complications that can occur in pregnancy due to COVID-19, one of which is abortion. Abortion in COVID-19 is associated with placental insufficiency caused by a virus and inflammation that occurs due to infection with virus of COVID-19. We report a case of abortion in pregnant women infected with COVID-19 with severe symptoms in inland area, the mountains of Papua.